Reduction Of The Chattering By Using Softned Several Ramps Control Law In The Field-Oriented Control Process Of An Induction Motor (Global Journals of Research in Engineering, 2012)
The aim of this paper is to propose a new control law for induction motor squirrel cage that is deemed by its strength, high torque mass, and its relatively low cost ... etc, meanwhile, it benefited from the support of industry since its invention. Despite these advantages, these actuators are complex dynamic systems that exhibit a strong non-linearity, which makes them difficult to control. So, the variable structure control is a solution for this problem because it is robust control despite the uncertainty on the model, disturbances and parametric variations. In practical applications, the main disadvantage associated with the command is the phenomenon of chattering. In order to minimize the amplitude of oscillations we propose a new technique of variable structure control which is softened several ramps. A simulation results revealed some very interesting features.
Keywords: Induction motor; field-oriented control; sliding mode control